2023
DOI: 10.1186/s12981-023-00525-z
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of bacterial LPS is associated with self-reported cognitive abilities in men living with HIV receiving antiretroviral therapy

Abstract: Background Gut damage allows translocation of bacterial lipopolysaccharide (LPS) and fungal β-D-glucan (BDG) into the blood. This microbial translocation contributes to systemic inflammation and risk of non-AIDS comorbidities in people living with HIV, including those receiving antiretroviral therapy (ART). We assessed whether markers of gut damage and microbial translocation were associated with cognition in ART-treated PLWH. Methods Eighty ART-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The depletion of these cells leads to an imbalance of the Th17/Treg ratio and enhanced production of cytokines, including IL-6, IL-17, IL-1β, IL-12, and IL-4, which disrupts epithelial junctions in the gastrointestinal mucosal barrier and therefore leads to increased microbial translocation [ 49 , 50 ]. There are known markers of microbial translocation, including plasma levels of lipopolysaccharide and soluble CD14, which are bacterial products, and (1➔3)-β-D-Glucan, a fungal product, that are elevated in untreated PLWH [ 51 , 52 ]. In addition to Th17 CD4 + lymphocytes, the decrease of mucosal-associated invariant T cells (MAIT) induced by chronic inflammation may contribute to increased susceptibility to microbial translocation.…”
Section: Modifiable Cvd Risk Factors In Plwhmentioning
confidence: 99%
“…The depletion of these cells leads to an imbalance of the Th17/Treg ratio and enhanced production of cytokines, including IL-6, IL-17, IL-1β, IL-12, and IL-4, which disrupts epithelial junctions in the gastrointestinal mucosal barrier and therefore leads to increased microbial translocation [ 49 , 50 ]. There are known markers of microbial translocation, including plasma levels of lipopolysaccharide and soluble CD14, which are bacterial products, and (1➔3)-β-D-Glucan, a fungal product, that are elevated in untreated PLWH [ 51 , 52 ]. In addition to Th17 CD4 + lymphocytes, the decrease of mucosal-associated invariant T cells (MAIT) induced by chronic inflammation may contribute to increased susceptibility to microbial translocation.…”
Section: Modifiable Cvd Risk Factors In Plwhmentioning
confidence: 99%
“…Convergent evidence indicates that PLWH display an altered composition of their intestinal microbiota and their by-products, a concept referred to as dysbiosis [2,3]. Gut barrier dysfunction (leaky gut) and the translocation of microbial products (endotoxins) into the systemic circulation have been linked with dysbiosis and non-AIDS comorbidities like cardiovascular disease, alterations of neurocognition, and cancer [1,[4][5][6][7][8][9]. We have showed that the elevated plasma levels of beta-D-glucan, a byproduct of fungi released from the gut into the circulating blood, were an LPS-independent contributor to inflammation in PLWH [10].…”
Section: Introductionmentioning
confidence: 99%